2013
DOI: 10.1074/mcp.m113.029330
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Analysis Reveals the Effects of PilF Phosphorylation on Type IV Pilus and Biofilm Formation in Thermus thermophilus HB27

Abstract: Thermus thermophilus HB27 is an extremely thermophilic eubacteria with a high frequency of natural competence. This organism is therefore often used as a thermophilic model to investigate the molecular basis of type IV pilimediated functions, such as the uptake of free DNA, adhesion, twitching motility, and biofilm formation, in hot environments. In this study, the phosphoproteome of T. thermophilus HB27 was analyzed via a shotgun approach and high-accuracy mass spectrometry. Ninety-three unique phosphopeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…S4). By means of affinity enrichment using this antibody, we identified 361 propionylation sites in 183 proteins, indicating that lysine propionylation is one of the most prevalent PTMs in T. thermophilus, comparable to acetylation and phosphorylation (33,45).…”
Section: Discussionmentioning
confidence: 99%
“…S4). By means of affinity enrichment using this antibody, we identified 361 propionylation sites in 183 proteins, indicating that lysine propionylation is one of the most prevalent PTMs in T. thermophilus, comparable to acetylation and phosphorylation (33,45).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial protein phosphorylation is required for the biosynthesis of capsular polysaccharides, biofilm development, virulence, and antibiotic resistance, particularly through two-component signaling systems (44,55,98,99). Thus, it has been demonstrated that His and Asp phosphorylation regulate the functions of pathogenesis, such as adherence, motility, enhancement of toxicity, quorum sensing, capsule formation, and drug resistance (100).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoproteomic analyses of SK17 were conducted using the shotgun LC-MS/MS approach to obtain large-scale data sets from biological triplicate experiments for each strain. Using the robust HAMMOC enrichment method and high mass accuracy LTQ-Orbitrap Velos, we identified 248 unique phosphoproteins with 351 phosphopeptides from SK17-S (supplemental Table S1), as well as 211 unique phosphoproteins with 240 phosphopeptides from SK17-R (supplemental Table S2) (34,44,54). Only 70 phosphoproteins overlapped in these two strains; 178 and 141 uniquely identified phosphoproteins were found in SK17-S and SK17-R, respectively ( Fig.…”
Section: Comparison Of a Baumannii Sk17-s And Sk17-r Phos-mentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument control was through Tune 2.6.0 and Xcalibur 2.1. Detailed settings for the Orbitrap analyzer followed a previous description [21]. …”
Section: Methodsmentioning
confidence: 99%